(untitled) (Global Journal of Science Frontier Research, 2015)
This study focus on the weak lines that appear on high energy side of the diagram lines which is called High Energy K X-ray hypersatellites i.e., a particular category of characteristic Xray due to splitting of fine structure levels. It’s resulted from the interaction of spin of an electron with the spin of the nucleus. They are emitted when an atom that has undergone a spontaneous transitions from the higher hyperfine level to the lower one to a radiation of ≈ 1.42 × 10 9 frequency and ≈ 21 wavelength. Simultaneous double ionization in the K-shell and multiple ionization in the L-shell gives rise to K α X-ray hypersatellites. These can be studied only by high energy resolution instruments like WDXRF spectrometry. Fundamental experimental procedures were outlined in this field by several workers due to different excitation modes. The theoretical models to predict their energies and intensities were developed. And also this review can show a clear discrepancy between theoretical and experimental results in the case of hyper satellites formation from different shells. In case of experimental instrumentation, WDXRF is the most accurate for determining the energy and intensity of X-ray hypersatellites. All sources of data was literature done by different scholars.